Pengaruh Motivasi Terhadap Kinerja Karyawan Melalui Servant Leadership Sebagai Variabel Mediasi Pada PT Salim Ivomas Pratama Tbk Perkebunan Balam, Kecamatan Balai Jaya, Kabupaten Rokan Hilir, Provinsi Riau - Ginting, Riska Mahdalena; Karim, Ahmad; Elanda, Yochi (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2026)
This study aims to analyze the effect of motivation on employee performance through servant leadership as a mediating variable at PT Salim Ivomas Pratama Tbk Balam Plantation, Balai Jaya District, Rokan Hilir Regency, Riau Province. This study employed a quantitative approach. The population in this study consisted of 739 employees, with a sample of 88 respondents determined using the Slovin formula and proportional random sampling technique. The data analysis techniques used included validity testing, reliability testing, classical assumption testing, and hypothesis testing consisting of t-test (partial), coefficient of determination test (R²), and Sobel test using SPSS version 27. The results of the study indicate that: (1) motivation has a positive and significant effect on employee performance, as evidenced by a t-value of 6.186 > t-table of 1.988; (2) motivation has a positive and significant effect on servant leadership, as evidenced by a t-value of 12.394 > t-table of 1.988; (3) servant leadership has a positive and significant effect on employee performance, as evidenced by a t-value of 4.840 > t-table of 1.988; and (4) servant leadership is able to mediate the effect of motivation on employee performance, as evidenced by a t-value of 4.507 > t-table of 1.988. The findings of this study indicate that motivation and servant leadership are important factors that can improve employee performance within the company.